Numerical modelling for quantitative environmental risk assessment for the disposal of drill cuttings and mud - Faiz Abdul Wahab, M.A. (Institute of Physics Publishing, 2017)
To investigate the fate of drilling waste and their impacts towards surrounding environment, numerical models were generated using an environmental software; MIKE by DHI. These numerical models were used to study the transportation of suspended drill waste plumes in the water column and its deposition on seabed in South China Sea (SCS). A random disposal site with the model area of 50 km × 25 km was selected near the Madalene Shoal in SCS and the ambient currents as well as other meteorological conditions were simulated in details at the proposed location. This paper was focusing on sensitivity study of different drill waste particle characteristics on impacts towards marine receiving environment. The drilling scenarios were obtained and adapted from the oil producer well at offshore Sabah (Case 1) and data from actual exploration drilling case at Pumbaa location (PL 469) in the Norwegian Sea (Case 2). The two cases were compared to study the effect of different drilling particle characteristics and their behavior in marine receiving environment after discharged. Using the Hydrodynamic and Sediment Transport models simulated in MIKE by DHI, the variation of currents and the behavior of the drilling waste particles can be analyzed and evaluated in terms of multiple degree zones of impacts. © Published under licence by IOP Publishing Ltd.